Strategic production and capacity planning in the guyabano leaf tea production of Olivares Organics and Natural Products Corporation - Felizardo, Karina O.; Lopez-Tan, Ma. Christina Beatrice F.; Naguit, Ma. Andrea V.; Orata, Mary Jef Rose D.
This study demonstrates a strategic capacity planning model of machine and labor resources for the the anticipated expansion of the Guyabano leaf tea production of Olivares Organic & Natural Products Corporation. An analysis of capacity requirements using single-station systems and machine cluster models was facilitated to determine the optimum number of machine units to meet the daily forecast demand, the optimum number of workers to effectively manage the machines, and the optimum worker-machine assignments that would minimize costs and maximize resource utilization. A key assumption used in the study is the constant production goal of 1,000,000 teabags daily which was based on OONPC's target rate for the planning horizon. Results showed that at the established level of forecast, OONPC would need 42 dehydrators managed by three workers, 2 crushers managed by one worker, 42 tea bagging machines manged by three workers, and 32 vacuum sealers managed by three workers on a one-to-one correspondence who are likeqise responsible for the manual boxing and final sealing of the products.